THE PHONETIC FEATURES OF SPEECH STYLES IN THE ENGLISH LANGUAGE - Fayzulloyeva Zilola Zafarovna,; Boturova Mexrangiz, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article examines the integral role of pronunciation in shaping the style of English speech and its impact on effective communication. It investigates how specific phonetic features—including intonation, stress, rhythm, and connected speech phenomena—contribute to the stylistic variation and expressiveness of spoken English. The discussion highlights the importance of suprasegmental elements over mere segmental accuracy, particularly in international contexts where intelligibility is paramount. Additionally, the article explores sociolinguistic dimensions, focusing on how pronunciation styles reflect speaker identity, social group affiliation, and adaptation to different communicative settings through style-shifting. The implications for English language teaching are considered, advocating for a broader approach that values pronunciation as a versatile tool for expressing meaning and social nuance rather than solely as a set of rigid norms. By addressing these interconnected factors, the paper provides insights into the dynamic relationship between sound and style that enriches English speech and facilitates successful interpersonal interaction.